EFFECT OF USING GUILLARD AND WALNE TECHNICAL CULTURE MEDIA ON GROWTH AND FATTY ACID PROFILES OF MICROALGAE Skeletonema sp. IN MASS CULTURE - Vivi Endar; . Sarjito; Johannes Hutabarat; Budi Prayitno (JOURNAL OF COASTAL DEVELOPMENT, 2012)
Live food, especially microalgae Skelotenoma sp. is a key success factor in shrimp aquaculture. To that end, the provision of Skeletonema sp. mass with a high nutrient content is needed. Nutritional quality of microalgae depends on the culture media used. The purpose of this study was to investigate effect of the use of different technical culture medium (Walne and Guillard) on the growth, protein content and fatty acid profile in microalgae culture Skelotenoma sp. Skeletonema sp. obtained from the Laboratory of Natural Feed BBPBAP Jepara. Culture method used was a mass with two different media (modified Walne and technical Guillard), with 12 replications. Data analysis were analyzed by using T test, while the protein content analysis was performed by Kjedahl method.The fatty acids were determined by using in situ transesterification. The results showed that the growth of Skeletonema sp. was markedly different between media Walne and technical Guillard. Guillard medium revealed lag phase after 44 hours (observation to 6) with a cell density of 48.00 x 104 cells/ml, then entered the exponential phase at 48. (Observation to 7) with a cell density of 70.25 x 104 cells / ml, while the stationary phase occurred in after hours to 52 (observation to 8) with a cell density of 86.75 x 104 cells / ml and death phase began at the 56 ( observations to 9) with a cell density of 54.58 x 104 cells / ml. Growth of Skeletonema sp. cultured with culture medium technical Walne showed a similar pattern in the lag phase to 44 hours of observation (observation to 6 with the cell density is 117.17 x 104sel/ml, exponential phase and stationary phase were detected from hour to 48 (observation to 7) with a cell density is 160.83 x 104 cells / ml. Later phases of death from an hour to 52 (observation to 8) with a cell density of 122.25 x 104 cells / ml. then long culvation or Skeletonema sp stationary phase in Guillard media over a period of 4 hours than Walne medium. Total fatty acids of Skeletonema sp. cultured in Guillard medium resulted in higher yields.